Annual reports in medicinal chemistry. Volume 34. - Doherty, Annette M. (Annette Marian), 1961-; ScienceDirect eBooks (San Diego, Calif. ; London : Academic Press, 1999)
Annual Reports in Medicinal Chemistry continues to strive to provide timely and critical reviews of important topics in medicinal chemistry together with an emphasis on emerging topics in the biological sciences which are expected to provide the basis for entirely new future therapies. Volume 34 retains the familiar format of previous volumes, this year with 33 chapters. Sections I-IV are disease-oriented and generally report on specific medicinal agents with updates from Volume 33 on antithrombotics, neurokinin receptor antagonists, anticoagualants, and new antibacterials. As in past volumes, annual updates have been limited to only the most active areas of research in favor of specifically focused and mechanistically oriented chapters, where the objective is to provide the reader with the most important new results in a particular field. Sections V and VI continue to emphasize important topics in medicinal chemistry, biology, and drug design as well as the critical interfaces among these disciplines. This volume concludes with To Market, To Market--a chapter on NCE and NBE introductions worldwide in 1998, a chapter on pharmagenomics, and finally one on malaria as a third world disease in need of a first world drug development.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Pharmaceutical chemistry -- Periodicals; Clinical chemistry -- Periodicals; MEDICAL -- Drug Guides; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; MEDICAL -- Nursing -- Pharmacology; Clinical chemistry; Pharmaceutical chemistry; Electronic books